The Role of Employee Engagement, Leadership, and Work Discipline in Enhancing Employee Performance - Mas Agung Tribratha Poernomo; Joko Suyono; Damarsari Ratnasahara Elisabeth; Aldrin Arizona Suyono (Indonesia Academia Research Society, 2025)
Employee performance is a crucial determinant of organizational effectiveness, particularly in public service institutions, where service quality depends heavily on employees' productivity and commitment. However, many organizations still face challenges maintaining high employee performance due to factors such as low employee engagement, ineffective leadership, and weak work discipline. This study aims to analyze the influence of employee engagement, leadership, and work discipline on employee performance. The research employed a quantitative, descriptive–explanatory design. The study was conducted at the Licin Community Health Center (PUSKESMAS) Licin in Banyuwangi, Indonesia, and involved all 51 employees as respondents, using a total sampling technique. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression in SPSS version 23. The results indicate that employee engagement, leadership, and work discipline each have a positive and significant effect on employee performance. Among the three variables, work discipline shows the strongest influence on employee performance, followed by leadership and employee engagement. These findings suggest that improving employee performance requires strengthening employee discipline, enhancing leadership effectiveness, and fostering greater employee engagement. Overall, the study highlights the importance of integrating organizational and behavioral factors to improve employee productivity and achieve sustainable organizational performance.